Assessment of swallowing function with oro‐pharyngeal‐esophageal scintigraphy in patients with idiopathic inflammatory myopathies. Issue 7 (23rd April 2019) - Barsotti, Simone; Puccini, Giulia; Tripoli, Alessandra; Cardelli, Chiara; Minichilli, Fabrizio; Volterrani, Duccio; Mosca, Marta; Grosso, Mariano; Neri, Rossella
Abstract: Background: Swallowing impairment is frequently present in patients with idiopathic inflammatory myopathies (IIMs), and it represents an important cause of morbidity, dramatically reducing the quality of life of patients. Moreover, dysphagia is associated to a worst prognosis. Unfortunately, no standardized instrumental techniques for the assessment of the upper gastrointestinal tract in IIM patients are available. In this study, we explored the characteristics of the alterations in the upper gastrointestinal tract using oro‐pharyngeal‐esophageal scintigraphy (OPES) in a cohort of IIM patients and we correlated the alterations with clinical parameters. Methods: A total of 51 IIM patients were examined with OPES, both with liquids and semisolids, and the data acquired were examined to compute the transit time and the percentage of retention at oral, pharyngeal, and esophageal level. Patient‐reported outcome data (PRO) on dysphagia, disease activity, and clinical parameters were collected. Key results: Oro‐pharyngeal‐esophageal scintigraphy identified at least one alteration in all patients, particularly with the semisolid test and oral and pharyngeal levels presented a higher frequency of involvement compared to the esophageal tract ( P < 0.05). A very good correlation between dysphagia severity assessed by PRO and many OPES results was identified. In patients with a shorter disease duration, there was a higher prevalence of alterations at the oral and pharyngeal level and they were correlated to higher swallowing difficulties and higher disease activity parameters. Conclusions & inferences: Our results showed that OPES may represent a novel reproducible tool to assess dysphagia in IIM patients, thus opening new possibilities to evaluate dysphagia in these patients. Abstract : Oro‐pharyngeal‐esophageal scintigraphy (OPES) may be useful for the diagnosis and evaluation of the severity of dysphagia in patients with idiopathic inflammatory myopathies. OPES may identify alterations of the upper digestive tract in a large proportion of patients even if asymptomatic, and may provide important information during the evaluation of myositis patients.